Nanostructure-induced fast texturization of mono-crystalline silicon in low-concentration alkaline solution. (May 2019) - Yang, Jiale; Shen, Honglie; Sun, Luanhong
Abstract: Silicon solar cells have been center of focus over the decades while the price challenge still hinders its large-scale application. Cost reduction is the urgent pursuit and our work focuses on the texturization process for mono-crystalline silicon. In this report, nanostructures made by metal-assisted chemical etching (MACE) method were introduced before texturization in low-concentration alkaline solution, which shows the advantage in controlling uniformity and thickness losses compared with standard-concentration alkaline solution. By varying MACE etching time, black silicon layers with different morphologies and depths were obtained. Consequently, pyramid structures of different sizes were observed after texturizaiton. Minimum reflectance value of 10.3% and mean pyramid size of 2.95 µm were achieved in low-concentration alkaline solution with optimized MACE etching time. By using SEM, PL and analytical balance to analyze the morphologies of black silicon samples and corresponding thickness losses, we speculated that the nanostructures of black silicon layers acted as the preferential sites for etching, thus accelerated the texturization process and completed within only 10 min. In summary, low-concentration, short-time and less silicon consumption texturization for mono-crystalline silicon could be achieved using our one-step MACE-induced method, exhibiting great potential in commercial photovoltaics utilization and ultra-thin silicon solar cells.